Interhospital transfer patients discharged by academic hospitalists and general internists: Characteristics and outcomes. Issue 4 (20th November 2015) - Sokol‐Hessner, Lauge; White, Andrew A.; Davis, Katherine F.; Herzig, Shoshana J.; Hohmann, Samuel F.
Abstract : BACKGROUND: Prior work suggests interhospital transfer (IHT) may be a risky event. Outcomes for patients transferred from another acute care institution and discharged by hospitalists and general internists at academic health systems are not well described. OBJECTIVE: Investigate the characteristics and outcomes of IHT patients compared with patients admitted from the emergency department (ED) to academic health systems. DESIGN: Retrospective cohort study. SETTING/PATIENTS: A total of 885, 392 adult inpatients discharged by hospitalists or general internal medicine physicians from 158 academic medical centers and affiliated hospitals participating in the University HealthSystem Consortium Clinical Database and Resource Manager from April 1, 2011 to March 31, 2012. METHODS: Patient cohorts were defined by admission source: those from another acute care institution were IHTs, and those coming through the ED whose source of origination was not another hospital or ambulatory surgery site were ED admissions. In‐hospital mortality was our primary outcome. We analyzed our data using descriptive statistics, t tests, χ 2 tests, and logistic regression. RESULTS: Compared with ED admissions, IHT patients had a longer average length of stay, higher proportion of time spent in the intensive care unit, higher costs per hospital day, lower frequency of discharges home, and higher inpatient mortality (4.1% vs 1.8%, P < 0.01). After adjusting for patient characteristics and risk of mortality measures, IHT patients had a higher risk of in‐hospital death (odds ratio: 1.36, 95% confidence interval: 1.29–1.43). CONCLUSIONS: In this large national sample, IHT status is independently associated with inpatient mortality. Journal of Hospital Medicine 2016;11:245–250. © 2015 Society of Hospital Medicine